CORPUS OF TITLE UNITS OF RUSSIAN-FOREIGN LANGUAGE REFERENCE BOOKS - Junying, Li; N. Karimullina, Rezeda; Rongguo, Gao (Gênero & Direito, 2019)
The object of research is linguistic informativity of the macrostructure of language reference books. The research material is bilingual (Russian-Tatar and Russian-Chinese) dictionaries of various types of the end of the 20th – beginning of the 21st cc. The paper presents the classification including various features of the existing bilingual dictionaries. Bilingual linguography comprises various types of anguage reference books. Most of the language reference books analyzed in this paper are monoscopal, with one source language and one target language. One of the key notions of linguography, as well as the essential component of a language reference book, is the vocabulary. One has to admit that in the modern linguography there is still no distinct objective criterion for selecting words for a language reference book. When composing a vocabulary, subjective factors play a great role. When researching the Russian-foreign language reference books, we revealed a number of mistakes and drawbacks referring to the vocabulary: a) unjustified inclusion of units into the vocabulary, b) unjustified absence of units in the vocabulary, c) orthographic mistakes, d) incorrect use of illustrative material (pictures, photos, etc.). There is no single established opinion as to what information a learner’s dictionary should include. It is important to remember that inclusion of specific information depends on the dictionary’s addressee and purpose.